Roles of eIF2α kinases in the pathogenesis of Alzheimer’s disease - Ohno, Masuo (Frontiers in Molecular Neuroscience, 2014)
Cell signaling in response to an array of diverse stress stimuli converges on the phosphorylation of eukaryotic initiation factor-2α (eIF2α). Evidence is accumulating that persistent eIF2α phosphorylation at Ser51 through prolonged overactivation of regulatory kinases occurs in neurodegenerative diseases such as Alzheimer’s disease (AD), leading to shutdown of general translation and translational activation of a subset of mRNAs. Recent advances in the development of gene-based strategies and bioavailable inhibitors, which specifically target one of the eIF2α kinases, have enabled us to investigate pathogenic roles of dysregulated eIF2α phosphorylation pathways. This review provides an overview of animal model studies in this field, focusing particularly on molecular mechanisms by which the dysregulation of eIF2α kinases may account for synaptic and memory deficits associated with AD. A growing body of evidence suggests that correcting aberrant eIF2α kinase activities may serve as disease-modifying therapeutic interventions to treat AD and related cognitive disorders.